Mantle deformation beneath the Western Ghats, India: Insights from core-refracted shear wave splitting analysis. (15th September 2021) - Sribin, C.; Padma Rao, B.; Ravi Kumar, M.; Tomson, J.K.
Graphical abstract: Left Panel: Composite SK(K)S and PK(K)S splitting measurements, plotted at the station locations. Brown coloured lines indicate composite splitting measurements from this study and those in green are the published ones. The lines are oriented in the fast axis polarization direction, with their lengths proportional to the delay times. Violet and Gray arrows point in the Absolute Plate Motion (APM) direction estimated from the NUVEL1A model, in a no-net rotation frame (DeMets et al., 1994) and HS3-NUVEL1A model, in a hotspot reference frame (Gripp and Gordan, 2002) respectively. Right Panel: Rose diagrams of the fast axis polarization directions. Red and blue colour indicates the APM parallel fast axis polarization directions and non-APM fast axis polarization directions respectively. Highlights: Fast axes of anisotropy vary from coast perpendicular to coast parallel, near and away from the west coast of India. Multilayer anisotropy beneath the southern part of Western Ghats. Non-APM fast axis polarization directions support multistage rifting and associated processes like edge flow. Abstract: The Western margin of the Indian sub-continent that hosts one of the world's largest escarpments, called the Western Ghats (WG), is a collage of diverse geological formations with different structural and physical properties. Characterizing upper mantle seismic anisotropy offers insights into the mantle deformation and its role in the evolution of such regions. In this study, we measured the upper mantle anisotropy using shear wave splitting analysis of SK(K)S and PK(K)S waveforms recorded at 17 broadband seismological stations located along and in the vicinity of the WG. Results indicate that the fast axis polarization directions are primarily in the NE-SW direction, with delay times varying from 0.3 s to 1.8 s. This direction is parallel to the Absolute Plate Motion of the Indian sub-continent, suggesting that shear at the base of the lithosphere is the dominant mechanism for anisotropy along the WG. E-W oriented anisotropy at stations close to the west coast, especially in the northern part of the WG can be associated with lithospheric stretching along the west coast, associated with the rifting process. Further, the coast-parallel fast axis polarization directions (N-S, NNW-SSE), with delay times varying from 0.6 s to 1.2 s, at stations away from the coast, could be due to the edge flow associated with transition from a thinner to a thicker lithosphere. In addition, we model the variation in splitting parameters at station PCH in the Southern Granulite Terran in terms of two-layer anisotropy, with an E-W orientation in the upper layer and a NE-SW one in the lower layer. The variable fast axis polarization directions from coast perpendicular to coast parallel at stations close and away from the west coast of the Indian sub-continent imply different rifting episodes.